A review of the recent advances on the treatment of industrial wastewaters by Sulfate Radical-based Advanced Oxidation Processes (SR-AOPs) - Giannakis, Stefanos; Lin, Kun-Yi Andrew; Ghanbari, Farshid (Chemical engineering journal (Lausanne, Switzerland : 1996), 2021)
[Display omitted] •The application of SR-AOPs for IWW treatment was systematically reviewed.•The theoretical (reactive species) and practical aspects (IWW composition) were analyzed.•SR-AOPs are vastly studied in landfill leachate and petrochemical IWW effluents.•Its advantages include the simultaneous HO/SO4− generation with non-radical pathways.•Limitations include the difficulty to apply heating, microwave and ultrasound activation. Over the last years, Sulfate Radical-based Advanced Oxidation Processes (SR-AOPs) have received considerable attention due to their high versatility and efficacy in disinfection and decontamination. Their advantages over classical AOPs, the generation of sulfate radicals (SO4∙-) from peroxydisulfate (PDS, S2O82-), or joint sulfate and hydroxyl radicals (HO∙) production from peroxymonosulfate (PMS, HSO5-) and their abundant activation methods have facilitated their introduction into various remediation and effluent decontamination processes. In this review, we present the advances in the field of industrial wastewater (IWW) treatment by SR-AOPs, by activation of either PMS or PDS via any suitable method, in homogeneous or heterogeneous (photo)catalytic processes. This review aims to present the state of the art in SR-AOPs application for IWW treatment, and act as a guideline of the field advances, summarize the previous application experiences, hence avoid research pitfalls and empower better IWW treatment practices. After an integrated presentation of the dominant pathways towards IWW decontamination, we discuss the SR-AOPs application in the treatment of effluents such as landfill leachate, petrochemical and pharmaceutical WW, pulp or paper industry effluents, textile and winery WW, as well as less studied processes such as coking, olive mill or soil washing effluents. Finally, the advantages and shortcomings of SR-AOPs for IWW treatment, as well as their perspectives are discussed.